Public and Private Regulation of Organ Transplantation: Liver Allocation and the Final Rule - Weimer, David L. (My University, 2006)
Private regulation governs how organs from cadavers are allocated. This process led to a change in the rules that more clearly define public and private roles. Several liver transplant centers prompted the Organ Procurement and Transplantation Network to adopt a national process for sharing organs. This paper examines the politics behind the decision and finds that private regulation makes effective use of stakeholders' technical expertise when changing the rules.